An innovative approach for manual preparation of slides of compact bone tissue - Singroha, Ritu; Verma, Usha (International Journal of Research in Medical Sciences, 2017)
Background: Bone is a rigid form of connective tissue in which the extracellular matrix is impregnated with inorganic salts, mainly calcium phosphate and carbonate, that provide hardness. Because of its hardness, bone is difficult to cut in the microtome; therefore, special techniques must be used for its study. Methods: Grinding of transverse sections of compact bone was done by using flint paper (size 0) which is simple, extremely cheap, rapid and easily available. Results: Under low power magnification, we observed a complete haversian system with volkmann’s canal and interstitial lamellae. Conclusions: This method of preparation of ground bone slides is not only helpful to undergraduate and post graduate students but also to osteoarchaeologists, palaeopathologists and forensic anthropologists.